Pengaruh Shift Kerja terhadap Stres Kerja pada Lima Orang Karyawan PT Asam Jawa, Kota Pinang - Batubara, Inggrid Mentari; Alifia Octaviani Aritonang; Batubara, Layla Hanum; Salianto, Salianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Occupational Health and Safety Branch (2008) explains that optimizing work shift arrangements can help reduce the potential health impacts on employees. Shift work involves various schedules and work patterns, and its arrangement must take into account a number of factors, such as the length of the shift or the number of hours worked per shift, team size, rest breaks, rotation periods or speed, and shift timing. The aim of this research is to determine the influence of shift work on the stress levels of PT Pegawai Asam Jawa employees in Kota Pinang, and whether there is a relationship between shift work variables and employee stress at PT Asam Jawa in Kota Pinang, using qualitative methodology. This study involved 114 participants. The research indicates that although morning shift workers do not experience high levels of stress, night shift workers do, resulting in decreased overall productivity in the afternoon and evening. Worker performance, health, and psychosocial issues are the subjects of these complaints. Except for night shift workers who complain of being less focused due to poor quality, there are no physical complaints experienced by morning shift workers and night shift workers in terms of body complaints, so the impact of shift work on employee stress can be observed.